DEVELOPMENT OF LEARNING VIDEO MEDIA ON BUILDING CONSTRUCTION BASIC LESSONS - Nova Riris Mendrova (LPPM Universitas Negeri Jakarta, 2022)
This study examines learning media on Building Construction Basic subjects, Occupational Safety and Health (OSH) material on Building Works.. Learning media are essential in the learning process, and good learning media are very effective in the teaching and learning process. In this case, the researcher tries to develop a learning video media that students can use using gadgets or laptops and androids through the storage media of CDs, flash drives, or other data/file storage places. It aims to facilitate students in understanding the material and facilitate the teacher's teaching process. In making this learning video media using the 4D model (Define, Design, Develop, Disseminate). This research was conducted in the google classroom application, while the sample in this study was 20 students of class X Modeling and Building Information Design Expertise Program, SMK Negeri 2 Binjai. The feasibility test of the media experts' developed instructional video media assessment showed an average rating of 3.80 and was declared